2006
DOI: 10.1667/rr3571.1
|View full text |Cite
|
Sign up to set email alerts
|

Protection of DNA against Direct Radiation Damage by Complex Formation with Positively Charged Polypeptides

Abstract: Radioprotection of DNA from direct-type radiation damage by histones has been studied in model systems using complexes of positively charged polypeptides (PCPs) with DNA. PCPs bind to DNA via ionic interactions mimicking the mode of DNA-histone binding. Direct radiation damage to DNA in films of DNA-PCP complexes was quantified as unaltered base release, which correlates closely with DNA strand breaks. All types of PCPs tested protected DNA from radiation, with the maximum radioprotection being approximately 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 51 publications
1
11
1
Order By: Relevance
“…A similar dependence was observed for the total base release, which can be correlated with DNA strand breaks, from polypeptide-DNA films irradiated by X-rays. 13 Studies on the radioprotection of DNA from direct damage by polypeptides have shown that poly-L-lysine protected DNA by a factor of approximately 2.5, while poly-L-arginine protected by a factor of 1.8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar dependence was observed for the total base release, which can be correlated with DNA strand breaks, from polypeptide-DNA films irradiated by X-rays. 13 Studies on the radioprotection of DNA from direct damage by polypeptides have shown that poly-L-lysine protected DNA by a factor of approximately 2.5, while poly-L-arginine protected by a factor of 1.8.…”
Section: Resultsmentioning
confidence: 99%
“…The studies on direct damage to complexes of positively charged polypeptides with DNA induced by X-rays showed that the degree of DNA radioprotection increases with a molar ratio of polypeptides. 13 These polypeptide-DNA complexes provide a better mimic of the cellular situation, where DNA is bonded to histones via ionic interactions. Moreover, recently it has been also shown that organic ions can prevent alterations in DNA induced by 10 eV electrons.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The first type is due to the attack of DNA by highly reactive radicals that are products of ionizations in the surrounding medium. However, the mobility of formed radicals is not significant and, additionally, the presence of radical scavengers in cells often protects the DNA molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular genomes are continuously damaged by reactive oxygen species through various processes 18 . An in vitro study showed that the binding of histones to DNA and their organization into higher-order chromatin structures dramatically protects DNA against hydroxyl radicalinduced DNA strand breaks as well as some types of radiation-induced damage [19][20][21] . This suggests that heterochromatin contributes to cellular defense against the induction of oxidative DNA damage 22,23 .…”
Section: Histone and Chromatin Structurementioning
confidence: 99%